2011
DOI: 10.5402/2011/107514
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants in Human Milk from Central Italy: Levels and Time Trends

Abstract: Persistent organic pollutants (POPs) such as HCB, p,p′-DDE, and PCBs were measured in Italian breast milk. This work is part of a study on human milk, adipose tissues, and food carried out in the same area over the last 20 years. The results showed the prevalence of p,p′-DDE and PCBs over HCB. Comparison of our results with those of previous studies carried out in the same area showed that concentrations are decreasing. No statistically significant differences in organochlorine levels were found when the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Organochlorines have been previously studied in human adipose tissue samples [16][17][18][19][20] and human milk [21] and mercury and organohalogen compounds have been determined in food and diet [22][23][24][25][26]. …”
Section: Introductionmentioning
confidence: 99%
“…Organochlorines have been previously studied in human adipose tissue samples [16][17][18][19][20] and human milk [21] and mercury and organohalogen compounds have been determined in food and diet [22][23][24][25][26]. …”
Section: Introductionmentioning
confidence: 99%
“…Perfluorooctanoic acid was extracted by use of an ion-pairing extraction procedure and measured by use of high-performance liquid chromatography (HPLC) with electrospray ionization tandem mass spectrometry, according to a widely used method [6,[26][27][28]. Perfluorooctanoic acid was extracted by use of an ion-pairing extraction procedure and measured by use of high-performance liquid chromatography (HPLC) with electrospray ionization tandem mass spectrometry, according to a widely used method [6,[26][27][28].…”
Section: Analysis Of Pfoa In Tissuesmentioning
confidence: 99%
“…Concentrations of PFOA in tissues were analyzed to determine the accumulation after 56 d of waterborne exposure. Perfluorooctanoic acid was extracted by use of an ion-pairing extraction procedure and measured by use of high-performance liquid chromatography (HPLC) with electrospray ionization tandem mass spectrometry, according to a widely used method [6,[26][27][28]. Approximately 1 g or 1 mL of sample was homogenized with 5 mL of Ultrapure water supplied by a Milli-Q system from Millipore.…”
Section: Analysis Of Pfoa In Tissuesmentioning
confidence: 99%
“…These studies summarized that most of the residual pesticides detected were below the respective maximal permissible limits set by international organizations, except [7] found that from five OCPs (alachlor, exchlorobenzene, dieldrin, methxychlor and linadane) and three OPPs (malathion, parathion-methyl and chlorpyrifos) identified in fresh buffalo milk of agro-industrial zone in upper Egypt, lindane and malathion exceeded EU limits. In other countries, China [8,9] and Italy [10] identified and quantified chlorpyrifos, bifenthrin, deltamethrin, lambda cyhalothrin, imidacloprid and carbofuran pesticides in different milk types from localities of Pakistan. Kara et al [11] investigated the Th presence of Th OPPs; malathion and Th malaoxon residues in Th buffalo and Th cow milk products in Th the Th western Turkey.…”
Section: Introductionmentioning
confidence: 99%